2013
DOI: 10.1016/j.eswa.2013.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Lost in PubMed. Factors influencing the success of medical information retrieval

Abstract: With the explosion of information available on the Web, finding specific medical information in an efficient way has become a considerable challenge. PubMed/MEDLINE offers an alternative to freetext searching on the web, allowing searchers to do a keyword-based search using Medical Subject Headings. However, finding relevant information within a limited time frame remains a difficult task.The current study is based on an error analysis of data from a retrieval experiment conducted at the nursing departments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…For many scientists, especially in the life-science domains, the literature retrieval process is tedious, error-prone and nontransparent [ 1 - 4 ]. On the other hand, the quality of literature search has been recognized as one of the key features for the generation of high quality scientific evidence [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For many scientists, especially in the life-science domains, the literature retrieval process is tedious, error-prone and nontransparent [ 1 - 4 ]. On the other hand, the quality of literature search has been recognized as one of the key features for the generation of high quality scientific evidence [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the quality of the query is strongly associated to the quality of the results. Vanopstal et al demonstrated that under-specified queries led to an increase of noise and our data show that under-specification is the main error compensated by querying in users’ first language [9]. An evaluation of the queries is planned as a second step.…”
Section: Discussionmentioning
confidence: 92%
“…On the contrary, in SimpleMed users were likely to rely on trial and error, which resulted in more query reformulations. Users with limited knowledge of medical terms tend to select incorrect terms and to adopt a completely new query based on trial and error (Vanopstal et al, ). MeshMed helps users replace inadequate terms with more correct ones, which could potentially reduce the iteration of reformulation attempts.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have explored the impact of contextual factors on users' query reformulation behavior (e.g., Liu, Gwizdka, & Belkin, ). Besides contextual factors, system features and interface design may have an impact on users' search behavior, and thus influence query reformulation behavior (e.g., Vanopstal, Buysschaert, Laureys, & Vander Stichele, ). This can be especially true in health IR, where users have been found to have difficulty in constructing effective queries due to the complex terminology system (Zeng, Kogan, Ash, Greenes, & Boxwala, ).…”
Section: Introductionmentioning
confidence: 99%